Running capacity of different genetic groups of bullocks - PARMAR, O S; BAHGA, C S (The Indian Journal of Animal Sciences, 2013)
Running capacity of Murrah buffalo (BM), Hariana CH), Holstein-Friesian x Hariana (HH), Jersey x local crossbred (JH), Holstein-Friesian x Sahiwal (37.5%-3/8 HS), Holstein-Friesian x Sahiwal (HS) and Brown Swiss x Sahiwal (BS) bullocks was measured on 2.5 km metalled track. The average speed of the bullocks completing a round was 8.1, 9.4, 9.7, 11.0, 12.2, 12.4 and 12.6 km/hr for BM, 3/8 HS,1/2 2HS, BS, JH, Hand HH respectively. The average speed of buffalo bullocks, and crossbreds of European breeds with Sahiwal and Hariana cows was 8.1, 10.03 and 12.4 km/hr respectively. Lowest speed (krn/hr) after running for 2 hr was observed in BM (3.29) followed by JH (3.40), BS (3.50), 1/2 HS (3.52), H (3.57), 3/8 HS (3.63), and HH (3.71). The decline in speed was highest for BM (28.48%). Average time (min) taken to complete a round was lowest in HH (11.9) followed by H (12.1), JH (12.3), BS (13.1), 1/2 HS (15.4), 3/8 HS (16.0) and BM (18.5). Fatigue score was highest for 1/2 HS (28.3), followed by BM (26.7), JH (23.4), 3/8 HS (21.5), HH (21.4), BS (21.3) and H (19.9). It can be concluded that the crossbred bullocks (Hariana x exotic breeds) were superior in running capacity as compared to crossbreds from Sahiwal cows and buffalo bullocks. Hariana purebred and HolsteinFriesian x Hariana crossbred bullocks were quite comparable for their running capacities.